Cash Holding, State Ownership and Firm Value: The Case of Vietnam - Do Thi Thanh Nhan; Pham Ha (International Journal of Economics and Financial Issues, 2016)
Using a sample of 650 listed firms on the Vietnamese stock exchange over the period 2008 to 2015, we examine the effect of cash holding level on firm value. The results find out the cash holding has an impact on firm value in an inverted U-shaped form. Furthermore, this study investigates whether the state ownership influences firm value. We point out that there is a statistically insignificant positive relationship between state ownership and firm value unless the state ownership's advantages are utilized. The findings have implications of cash management in state-owned firms.